Association study between (rs1799750) polymorphism and periodontal by Tetra arms-PCR - Mohadese Baghdadchi; Elham Siasi Torbati; Kumars Amini (Tehran University of Medical Sciences, 2020)
Background and Aims: Periodontitis is one of the most common causes of damage to the gums and retaining structures of the teeth. Matrix protein, a metalloproteinase, is known as intermediate collagenase and the enzyme collagenase fibroblast, which is encoded in humans by the MMP-1 gene. The aim of this study was to investigate 1G/2G polymorphism in the MMP-1 gene and its association with the periodontal disease in the Iranian patients. Materials and Methods: In this study, 50 patients with periodontal disease and 50 patients were selected as the control group in Kerman city. DNA was extracted from a personchr('39')s blood sample using a kit. The desired primers were controlled by the NCBI site. Then, with the Tetra arms PCR technique, the desired polymorphism was multiplied. In the next step, the samples were transferred to electrophoresis gel and examined. The results were analyzed with SPSS software using T-test or Squer Chi-(X2). Results: The percentage of 1G/1G genotype in the patients group was 8% and for the controls group was 0%. The percentage of 2G/2G genotype for the patients group was 24% and for the controls group was 18%. In addition, the 1G/2G genotype frequency was 68% for the patients group, and for the controls group was 82% (P=0.83). The results of Tetra-arms PCR genotyping of the samples were confirmed by sequencing. Conclusion: The findings indicated that in Iranian patients, MMP-1 -1607 1G/2G (rs1799750) was not significantly associated with periodontal disease. It is recommended to take more samples from different parts of Iran to confirm the results.